TOKSISITAS BIOINSEKTISIDA EKSTRAK KULIT JERUK TERHADAP KUTU LONCAT JERUK Diaphorina citri Kuwayama (Hemiptera: Psyllidae) SEBAGAI VEKTOR PENYAKIT CVPD - Wuryantini, Susi; Harwanto, Harwanto; Yudistira, Rizky Arya (JURNAL AGRONIDA, 2019)
Diaphorina citri is an important pest in citrus plants because of its role as a vector of Citrus Vein Phloem Degeneration (CVPD) disease. The study was a follow-up test of the preliminary tests carried out previously. The aim of this study was to determine the effective concentration of bioinsecticide of Japansche Citroen (JC) orange peel extract in controlling D. citri in the phases of nymph and imago. The concentration tested was 0% (control); 0.01%; 0.1%; 1%; and 10% (v / v) with a comparison of imidacloprid insecticide 0.1%. The test results showed that the JC citrus peel extract at a concentration of 0.1 effectively controlled the D. citri nymph starting at 96 hours after application (HAA) with a mortality of 69%. The concentration of 1% was effective from 24 HAA with a mortality of 65% and thereafter reaching up to 100% at 120 HAA, this was not significantly different from the 10% concentration treatment and imidacloprid insecticide 0.1%, yet was significantly different from other treatments and controls. Citrus peel extract was effective for controlling imago of D. citri on 10% concentration. The concentration that was able to provide mortality above 50% was the highest concentration of 10% at 96, 120 and 144 HAA. The results of the probit analysis showed that the LC50 values at 24 HAA on nymphs was 1.86 and the LC90 value was 9.10. The treatment on imago the LC50 at 48 HAA was 21.34 and the LC90 was not achieved. The results of the calculation of the LC50 and LC90 values showed that the value in nymphs was smaller than in imago. This showed that the bioinsecticide of JC citrus peel extract was more effective against nymphs than imago of D. citri. Bioinsecticide of JC citrus peel extract was effective against psyllid nymph of D. citri at concentrations of 0.1 and 1% and against the imago phase was effective at 10%. Keywords: Toxicity, citrus peel extract, Diaphorina citri